A New Spiralian Phylogeny Places the Enigmatic Arrow Worms among Gnathiferans - Marlétaz, Ferdinand; Peijnenburg, Katja T.C.A.; Goto, Taichiro; Satoh, Noriyuki; Rokhsar, Daniel S. (Current biology, 2019)
Chaetognaths (arrow worms) are an enigmatic group of marine animals whose phylogenetic position remains elusive, in part because they display a mix of developmental and morphological characters associated with other groups [1, 2]. In particular, it remains unclear whether they are a sister group to protostomes [1, 2], one of the principal animal superclades, or whether they bear a closer relationship with some spiralian phyla [3, 4]. Addressing the phylogenetic position of chaetognaths and refining our understanding of relationships among spiralians are essential to fully comprehend character changes during bilaterian evolution [5]. To tackle these questions, we generated new transcriptomes for ten chaetognath species, compiling an extensive phylogenomic dataset that maximizes data occupancy and taxonomic representation. We employed inference methods that consider rate and compositional heterogeneity across taxa to avoid limitations of earlier analyses [6]. In this way, we greatly improved the resolution of the protostome tree of life. We find that chaetognaths cluster together with rotifers, gnathostomulids, and micrognathozoans within an expanded Gnathifera clade and that this clade is the sister group to other spiralians [7, 8]. Our analysis shows that several previously proposed groupings are likely due to systematic error, and we propose a revised organization of Lophotrochozoa with three main clades: Tetraneuralia (mollusks and entoprocts), Lophophorata (brachiopods, phoronids, and ectoprocts), and a third unnamed clade gathering annelids, nemerteans, and platyhelminthes. Consideration of classical morphological, developmental, and genomic characters in light of this topology indicates secondary loss as a fundamental trend in spiralian evolution. •Chaetognaths are gnathiferans, the sister group to other spiralians•Lophotrochozoans are divided in three main clades, including Tetraneuralia•A new clade is made of annelids, nemerteans, and platyhelminths•Compositional heterogeneity affects the reconstruction of the protostome tree Marlétaz et al. used new data and refined methods to improve the phylogenetic placement of chaetognaths, an enigmatic group of marine animals. They relate to gnathiferans, a sister group of other spiralians, and include rotifers and gnathostomulids. Spiralians are subdivided in three main clades (including Tetraneuralia and Lophotrochozoa).